Analysis of Road Conditions In The Kaligunting-Bajulan Section Using The Pavement Condition Index (PCI) Method - Salman At Taufan; Risma Marleno; Wateno Oetomo (Asian Journal of Social and Humanities, 2025)
This study evaluates the road condition of the Kaligunting-Bajulan section in Madiun Regency using the Pavement Condition Index (PCI) method. The goal is to assess the level of deterioration, identify repair needs, and estimate costs. The findings reveal that the road is in moderate to poor condition, with the average PCI score of 58.08, highlighting the need for immediate intervention, particularly in segments with the most severe damage. The research employs a combination of field surveys, visual assessments, and drone technology to ensure accurate data collection. The study recommends a cost-efficient repair strategy that includes sealing and repaving damaged sections. This approach helps prioritize road segments based on damage severity and traffic load, ensuring that maintenance efforts are focused on the most critical areas. By utilizing the PCI method, the study offers a transparent and measurable framework for local governments to allocate repair budgets more efficiently, ensuring improved road safety and longer infrastructure lifespan. This research supports the implementation of preventive maintenance strategies and presents a replicable model for managing road infrastructure in other regions with similar challenges.